REVISION ANALYSIS FACTORS THAT INHIBIT THE DEVELOPMENT OF SMALL AND MEDIUM ENTERPRISES IN THE GRAPHIC DESIGN SECTOR (CASE STUDY OF EDUCATED MILLENNIALS) - Khusnul Ashar; Hafidz, Hafidz Ash Shalih (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
The graphic design industry is a very promising and very flexible industry along with the development of technology and also the use of social media among the public. Departing from this, it was found that small and medium enterprises engaged in graphic design, especially millennials, caused great market competition. This has resulted in many graphic design businesses that are unable to develop or even regress. But behind the high market competition, there are still many graphic design businesses that are still able to maintain their existence or even develop. Departing from this, the purpose of this research is to determine the factors that hinder the development of graphic design businesses. There are 6 factors that can hinder business development, namely Human Resources (HR) factors, Planning Factors, Marketing and Sales Factors, Business Management Factors, Venture Capital, and Government Assistance. This study used qualitative descriptive analysis method with data collection techniques through interviews. Based on the analysis of results / findings in the field, researchers can conclude that there are 5 factors that hinder the development of graphic design businesses, especially the millennial sector, namely Human Resources (HR) factors, Planning Factors, Marketing and Sales Factors, Business Management Factors, Business Capital While government assistance is considered influential. The results of this study can be used as a basis for taking policies for graphic design business owners specifically for the millennial sector to improve their business development and can also be used as a learning for prospective entrepreneurs, especially in the field of graphic design. Keywords: Graphic Design, MSMEs, Millennials